Non-traumatic shoulder instability measurements from accelerometer and audio records - Espinosa, H. G.; McDonough, E.; Thiel, D. V. (Journal of Fitness Research, 2016)
Accelerometer sensors used to determine limb movement have significant high frequency noise levels which are often ignored and removed by low pass filtering. This preliminary investigation reports the relationship between audible shoulder events and accelerometer measurements at the shoulder and the wrist during repeated flexion and extension of the arm with a 3 kg weight. Repeated cycles show audio events (clicks) which strongly correlate with high frequency acceleration events at the same arm inclination angle and leads to an explanation of some of the high frequency acceleration events during rhythmic movements such as ballet.